Adaptive Performance as a Dimension of Job Performance: A Theoretical Framework - Ümit Dilekçi; Şenay Sezgin Nartgün (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The aim of this study is to examine the concept of adaptive performance within atheoretical perspective. For this purpose, jobperformance was first mentioned and the concepts of task performance,contextual performance and counterproductive performance, which are among the dimensions of jobperformance, were briefly mentioned, and then the concept of the adaptiveperformance was discussed. When the literature is examined, it is seen thatadaptive performance is frequently discussed together with the concepts ofchange and adaptability, and by referring to the emergence and thedevelopmental process of adaptive performance, the difference between adaptiveperformance and other dimensions of job performance is emphasized and adaptiveperformance is defined. Therefore, the concept of adaptive performance in thestudy is examined under four subtitles as change,adaptability, the emergence of adaptive performance and developmental process, definingadaptive performance. Then, the concepts that are evaluated as sub-dimensionsof adaptive performance were explained. In discussion and conclusion, the termadaptive performance is handled in the context of educational organizations andthe teaching profession.